Neuromodulation techniques – From non-invasive brain stimulation to deep brain stimulation - Davidson, Benjamin; Bhattacharya, Amitabh; Sarica, Can; Darmani, Ghazaleh; Raies, Nasem; Chen, Robert; Lozano, Andres M. (Neurotherapeutics, 2024)
Over the past 30 years, the field of neuromodulation has witnessed remarkable advancements. These developments encompass a spectrum of techniques, both non-invasive and invasive, that possess the ability to both probe and influence the central nervous system. In many cases neuromodulation therapies have been adopted into standard care treatments. Transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), and transcranial ultrasound stimulation (TUS) are the most common non-invasive methods in use today. Deep brain stimulation (DBS), spinal cord stimulation (SCS), and vagus nerve stimulation (VNS), are leading surgical methods for neuromodulation. Ongoing active clinical trials using are uncovering novel applications and paradigms for these interventions.